Analisis kekuatan tarik, kekerasan dan struktur mikro pada pengelasan SMAW yang menggunakan elektroda E 6013 dengan variasi gerakan elektroda - Andri Santoso; Awal Syahrani; M Mustafa (Badan Kerja Sama Teknik Mesin Indonesia, 2018)
This study aims to determine the effect of electrode motion on the mechanical properties and microstructure of SMAW welding with E 6013 electrode. The SMAW welding process uses a variety of straight, zigzag and spiral electrode movements. The electrode used is E 6013 with a diameter of 3.2 mm. The current size used is 90 Amperes. The type of camp used is a V-shaped with an angle of 60o, a root height of 2 mm and a root range of 3 mm. Tests conducted are tensile testing, hardness and microstructure observation. The highest tensile strength value in the spiral electrode motion is 616.6 Mpa and the lowest in the zig-zag electrode is 596 MPa. While the highest strain value found in the motion of zig-zag electrode is 22.91% and the lowest in the spiral electrode movement is 19.41%. For the highest modulus of elasticity is found in the straight electrode movement of 12070.02 Mpa and the lowest in the motion of the zigzag electrode is 10339,48 Mpa. The highest hardness value is in welding with zigzagging electrode movement that is 147,44 kg / mm2 and the lowest in straight electrode movement is 143,19 kg / mm2